Generative and Transformational Techniques in Software Engineering II International Summer School, GTTSE 2007, Braga, Portugal, July 2-7. 2007, Revised Papers - Lämmel, Ralf; Visser, Joost; Saraiva, João (Programming and Software Engineering, 2008)
This tutorial book presents an augmented selection of the material presented at the International Summer School on Generative and Transformational Techniques in Software Engineering, GTTSE 2007, held in Braga, Portugal, in July 2007. The 7 tutorial lectures presented together with 5 short tutorials and 4 contributions to the participants workshop were carefully selected during multiple rounds of reviewing and improvement. The tutorials given by renowned representatives of complementary approaches and problem domains combine foundations, methods, examples, and tool support.